Myocardial work comes to rescue when afterload-dependency of strain cause false positives. (8th February 2021) - Sletten, OJ; Aalen, JM; Remme, EW; Khan, FH; Hisdal, J; Smiseth, OA; Skulstad, H
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): The Norwegian Health Association Introduction: Global longitudinal strain (GLS) can detect subclinical left ventricular (LV) dysfunction. GLS measurement is therefore recommended when chemotherapy-induced cardiotoxicity can be suspected. A relative, percentage reduction in GLS ≥8% may indicate subclinical LV dysfunction induced by chemotherapy. Due to afterload-dependency, moderate increase in blood pressure has the potential to cause reductions in GLS beyond this threshold. However, myocardial work incorporates afterload, and may be used to omit false positive outcomes. Purpose: To investigate if moderate increases in afterload cause clinically relevant changes in strain, and if myocardial work is more robust to such changes. Methods: Twenty cancer patients (41 ± 14 years) undergoing chemotherapy and twenty healthy controls (49 ± 11 years, NS) were included. All participants were free from concomitant heart disease. GLS was measured by speckle-tracking echocardiography. Global myocardial work was calculated by pressure-strain analysis using a previously validated method to estimate LV pressure (LVP) non-invasively. Recordings were performed before and after 2 minute stress by handgrip. Results: At baseline, patients had lower GLS (20.1 ± 1.1 vs 22.1 ± 2.5%, p < 0.01) and global myocardial work (1810 ± 203 vs 2051 ± 287 mmHg·%, p < 0.01) than controls. Stress test moderately increased systolic blood pressure, similar in both groups (116 ± 10 to 146 ± 17 mmHg in patients, and 118 ± 12 to 147 ± 21 mmHg in controls). This afterload-enhancement was associated with a decrease in GLS from 20.1 ± 1.1 to 18.4 ± 1.3% in patients, and from 22.1 ± 2.5 to 20.3 ± 2.5% in controls (both p < 0.01). Every second participant, eleven patients and nine controls, experienced a relative reduction in GLS >8%. In contrast, global myocardial work increased during the stress test from 1810 ± 203 to 2002 ± 281 mmHg·% in patients, and from 2051 ± 287 to 2292 ± 398 mmHg·% in controls (both p < 0.01). Figure 1 shows changes in GLS and myocardial work at moderate increase in afterload. Conclusions: Moderate increase in afterload caused reductions in GLS sufficient to promote over-diagnosis of chemotherapy-induced cardiotoxicity. Global myocardial work has the potential to distinguish true subclinical LV dysfunction from afterload-induced decline in GLS.